Transfusion Reaction Identification and Management at the Bedside. Issue 2 (March 2015) - Crookston, Kendall P.; Koenig, Sara C.; Reyes, Michael D.
<x xml:space="preserve">Abstract</x> Blood product transfusion is one of the most common invasive procedures performed in the health care setting. In contrast to pharmaceuticals, blood is actually a liquid transplant. Transfusion complications consequently encompass complex biological processes and infectious possibilities. Changes in vital signs are regularly seen during transfusion. Knowledge of common transfusion reaction signs and symptoms enables the clinical team to differentiate a normal patient response from a life-threatening reaction. Direct care nurses responsible for this procedure play a vital role in its success. Understanding the possible complications of transfusion and how to quickly recognize reactions at the bedside helps ensure the best patient outcomes.